1969
DOI: 10.1037/h0028209
|View full text |Cite
|
Sign up to set email alerts
|

Delayed matching-to-sample and short-term memory in the capuchin monkey.

Abstract: A delayed matching-to-sample paradigm (DMTS), employing a visual task in which Ss (capuchin, monkeys) could not fall back on mediating behaviors of a positional or orientational nature, was used to investigate interference phenomena in short-term memory (STM). Sample-set size, i.e., the number of stimuli used (two, three, or four), was varied orthogonally with delay interval (1, 3, 9, or 18 sec.). Within the parametric limitations of the experiment no evidence for STM interference effects was found. Based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…The three subjects, Pete, Basil, and Roscoe, all adult male capuchin monkeys (Cebus apella), had served in earlier studies of delayed matching (Etkin, 1970;Etkin and D'Amato, 1969). During the present experiment, they were maintained at 85 to 95% of their full-ration body weight.…”
Section: Subjectsmentioning
confidence: 99%
“…The three subjects, Pete, Basil, and Roscoe, all adult male capuchin monkeys (Cebus apella), had served in earlier studies of delayed matching (Etkin, 1970;Etkin and D'Amato, 1969). During the present experiment, they were maintained at 85 to 95% of their full-ration body weight.…”
Section: Subjectsmentioning
confidence: 99%
“…Thus, the present article describes the equipment and procedures for such an automated, appetitive, free-operant conditioning task in zebrafish similar to those that have been used for decades in birds, rodent, and primates. [23][24][25] The development of these procedures required overcoming several challenges. First, because adult zebrafish are very small for being used in appetitive conditioning studies, satiation can occur quickly which presents a problem.…”
Section: Introductionmentioning
confidence: 99%
“…David Premack had concluded that "Why it would be difficult to talk to a pigeon" was because pigeons are incapable of same/different abstract-concept learning; he also offered the same conclusion for other nonlanguagetrained animals (Premack 1978(Premack , 1983Premack & Premack, 1983). The ability to judge two things as either the same or different does have a special role in the development of human abstract cognitive thinking (e.g., equivalence, conservation of area, volume, and number: Daehler & Bukatko, 1985;Marcus, Vijayan, Bandi Rao, & Vishton, 1999;Piaget & Inhelder, 1966/1969Siegler, 1996). Such abstract thinking forms the rudimentary basis of mathematical operations based on equivalence.…”
mentioning
confidence: 95%
“…By using completely novel stimuli, as did Overman and Doty (1980) Overman & Doty, 1980Etkin & D'Amato, 1969Moise, 1976Roberts & Grant, 1976 Fig. 1.…”
mentioning
confidence: 99%